2018
DOI: 10.21726/rsbo.v1i3.482
|View full text |Cite
|
Sign up to set email alerts
|

Oral evaluation of children and adolescents in intensive care unit

Abstract: Introduction: Hospitalized children can present some complications if they do not present a correct oral care during hospitalization. Objective: This study aimed to perform an oral evaluation of children and adolescents hospitalized in an intensive care unit of a children's hospital at southern Brazil. Material and methods: 49 subjects were examined, aged from 0 to 17 years old, using the modified Oral Assessment Guide (OAGm). The lips, corner of the mouth, gums, oral mucosa, saliva, tongue, and teeth were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(21 citation statements)
references
References 11 publications
2
18
1
Order By: Relevance
“…The literature also suggests that, as age increases, oral health changes become more likely to occur in hospitalized patients. 7 This study found that the mean OAG scores of the patients ≥61 months or older were higher than those of the patients 60 months or younger, and their oral health status worsened accordingly. This finding is similar to that reported by Schunemann et al 7 The teeth are known as a host for dental plaques, which are also a favorable site for harmful pathogens.…”
Section: Investigation Of the Descriptive Characteristics Of Patientsmentioning
confidence: 58%
See 4 more Smart Citations
“…The literature also suggests that, as age increases, oral health changes become more likely to occur in hospitalized patients. 7 This study found that the mean OAG scores of the patients ≥61 months or older were higher than those of the patients 60 months or younger, and their oral health status worsened accordingly. This finding is similar to that reported by Schunemann et al 7 The teeth are known as a host for dental plaques, which are also a favorable site for harmful pathogens.…”
Section: Investigation Of the Descriptive Characteristics Of Patientsmentioning
confidence: 58%
“…A patient information form was prepared in line with the literature to assess the patients' descriptive characteristics. [2][3][4]7,19,20 The Oral Assessment Guide (OAG) was developed by Gibson et al 21 in 2006. Çiftcioğlu and Efe 22 evaluated and confirmed the validity and reliability of the Turkish version of the OAG.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 3 more Smart Citations